Projection of future climate change in the Poyang Lake Basin of China under the global warming of 1.5–3°C - Zhang, Meng; Xu, Wanling; Hu, Zengyun; Merz, Christoph; Ma, Miaomiao; Wei, Jianhui; Guan, Xiaojun; Jiang, Lizhi; Bao, Ruijuan; Wei, Yingying; Gao, Lu (Frontiers in Environmental Science, 2022)
This study projected the future climate changes in the Poyang Lake Basin (PLB) of China under various global warming targets (1.5-3℃), based on the latest Coupled Model Intercomparison Project Phase 6 (CMIP6) and 4 statistical downscaling methods, including Quantile Mapping (QM), Daily Translation (DT), Delta, and Local Intensity Scaling (LOCI). The RMSE, R2 and KGE indicators were used to evaluate the competency of the aforementioned methods applied to daily precipitation (Pre), daily mean temperature (Tas), daily maximum temperature (Tasmax), and daily minimum temperature (Tasmin). The global warming of 1.5, 2 and 3℃ will occur around 2040, from 2045 to 2080 and around 2075, respectively, for the emission scenarios of SSP1-2.6, SSP2-4.5, SSP3-7.0 and SSP5-8.5. The results demonstrated that under the 1.5, 2 and 3℃ global warming targets, the projected annual precipitation declined by 14.82, 11.92 and 8.91% relative to the reference period (1986-2005), respectively. The Tas increased significantly by 0.43, 0.94 and 1.92℃ and the Tasmax increased by 0.58, 1.11 and 2.09℃. The Tasmin decreased by 0.29℃ under the 1.5℃ warming target, while it increased by 0.19 and 1.18℃ under the 2 and 3℃ warming targets. The spatial distributions of future annual precipitation in the PLB were relative consistent. However, the regional variability was significant, which the southern and eastern regions experienced more precipitation than the northern and western regions. The south-central part of the Ganjiang basin was the high-value area while the northeastern part was the low-value area. The Tas, Tasmax and Tasmin had a consistent spatial variation characteristic that the high latitude areas were warmer than the low latitude areas, and the western regions were warmer than the central and eastern regions while the northeastern regions were cooler than the remaining regions.